(untitled) (Comprehensive Journal of Science, 2025)
The paper is contains on sum of mean points related to the role of administrative reforming in sustainable development , it takes logical steps to views this stages of the study. at the beginning concentrate on the concepts of sustainable development, institutional reforming generally, its properties , programs , which it gives to the countries which suffering from the retardation , then throw light on the difficulties of both reforming programs and social development in this kind of societies with some examples to this problems. . In addition , identify the cultures factors and its impact on this countries , finally view the challenges which facing this programs reforming ,the study use the questionnaire to collect the data of the study, and collect data by the comprehensive survey method, then use the( spss), to analyze the data, the result proves that institutional reform has role to achieving sustainable development .